PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan Joint Operating Body Pertamina-PertoChina East Java) - Widhayu Ningrum (Fakultas Ilmu Administrasi Universitas Brawijaya, 2013)
The purposes from this research are Knowing and explaining of influences to the employee ‘s education significantly (X1) and employee’s training (X2) through the employee’s performance (Y), Knowing and explaining the employee’s education influences (X1) Employee’s Performance (Y), Knowing and Elaborating the employee’s training influences (X2) to the employee’s performance (Y). Types of this research are Explanatory with Independent Variable which consists of Employee’s Education (X1) and Employee’s Training (X2) which consists of Dependent Variable Employee’s Performance (Y). samples have been taken from using Proportional Random Sampling which derives from the population totally 166 employees and has been obtained by 62 employees. Data have been analyzed further accurately by using Classic Assumption Test, Double Linear Regression Analysis Hypothesis test which supported with Computer SPSS Version 17 for windows programs. The results can be known by Employee’s Education (X1) and Employee’s Training (X2) have significant influences to the employee’s performance (Y), amazingly shown with Value F ( 31, 571 ) > Value T ( 2,23 ), even though by using Partial Test Method, Meanwhile Employees Education variabel (X1)has been given Value 0,043 and Employee’s Training Variable (X2) has been value 0,000. Keyword : Employee’s Education, Employee’s Training, Employee’s PerformanceABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui dan menjelaskan pengaruh signifikan pendidikan karyawan dan pelatihan karyawan terhadap kinerja karyawan, mengetahui dan menjelaskan pengaruh pendidikan terhadap kinerja karyawan, mengetahui dan menjelaskan pengaruh pelatihan karyawan terhadap kinerja karyawan. Jenis penelitian adalah Explanatory dengan dua variabel independen yang terdiri dari pendidikan karyawan (X1) dan pelatihan karyawan (X2) serta variabel bebas kinerja karyawan (Y). Sampel yang diambil menggunakan metode Proportional Random Sampling dari populasi sebanyak 166 karyawan dan diperoleh sampel 62 karyawan. Data yang terkumpul selanjutnya dianalisis dengan menggunakan Uji Asumsi Klasik, Analisis Regresi Linier Berganda, Uji Hipotesis, dengan bantuan program SPSS Version 17 For Windows. Hasil penelitian dapat diketahui bahwa pendidikan karyawan dan pelatihan karyawan mempunyai pengaruh signifikan terhadap kinerja karyawan ditunjukkan nilai Fhitung = 31,571 > Ftabel = 2,23, demikian pula dengan uji parsial dengan uji t, untuk variabel pendidikan karyawan (X1) diperoleh nilai 0,043 dan untuk variabel pelatihan karyawan (X2) diperoleh nilai 0,000. Kata kunci : Pendidikan Karyawan, Pelatihan Karyawan, Kinerja Karyawan